Isolation and characterization of endothelial progenitor cells from canine bone marrow. (17th February 2021) - Chen, Chen; Dai, Pengxiu; Nan, Liangliang; Lu, Ruiqing; Wang, Xiuyuan; Tian, Yuanyuan; Zhang, Xinke; Gao, Yongping; Zheng, Shuxin; Zhang, Yihua
ABSTRACT: Endothelial progenitor cells (EPC) are located predominantly in the bone marrow. These cells are useful for treating human vascular diseases; they also are a possible target for restricting blood vessel growth for tumors. Little is known about canine EPC. We investigated a bone marrow EPC isolation method that combines the whole bone marrow culture method and the differential adherent speed method using stillborn canines. MTT proliferation, flow cytometry detection, Dil-ac-LDL uptake, FITC-UEA-1 binding and matrigel assays were used to identify and characterize EPC. We isolated two types of EPC: early EPC and late EPC. We found that isolated cells produced typical colony and cobblestone morphology, and were positive for CD31, CD34, CD133 and VEGFR-2. Significant differences were observed in the intensity of expression between early and late EPC, which suggests their different roles during angiogenesis and vasculogenesis. Both early and late EPC were positive for Dil-ac-LDL and FITC-UEA-1, and displayed tube formation when re-suspended in matrigel, both of which are important functional criteria for identifying EPC. Our method is a novel, effective and efficient way to produce enriched EPC.